1995
DOI: 10.1021/ma00111a057
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Stabilization of Ultrathin Polymer Films Prepared by the Langmuir-Blodgett Technique

Abstract: Photoreactive Langmuir-Blodgett films were made of poly(vinyl octanal acetal-co-vinyl cinnamate) (P(VO-VC)), and the effect of photo-cross-linking on the stability of a layered structure against thermal and chemical treatments has been demonstrated by energy transfer and surface plasmon spectroscopy. Photochemical cross-linking in P(VO-VC) layers easily occurred by UV irradiation for a few minutes, and consequently, the polymer became insoluble in a good solvent, dichloromethane. The durability against the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In addition, in some cases, it has been shown that the stability of a polymer Langmuir monolayer can be strengthened through cross-linking reactions performed either in situ or after monolayer transfer onto a substrate. Well-ordered two-dimensional (2D) polymer networks have also been synthesized starting from monomers. In some cases, improved mechanical or thermal properties are evidenced. ,, Among the different reaction pathways available, free-radical cross-linking using UV irradiation is the main mechanism used at the air–water interface. Indeed, UV light has the advantage of simplicity of use, avoiding the introduction of a cross-linking agent in the subphase and allowing a spatial control of the reaction at a local scale .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in some cases, it has been shown that the stability of a polymer Langmuir monolayer can be strengthened through cross-linking reactions performed either in situ or after monolayer transfer onto a substrate. Well-ordered two-dimensional (2D) polymer networks have also been synthesized starting from monomers. In some cases, improved mechanical or thermal properties are evidenced. ,, Among the different reaction pathways available, free-radical cross-linking using UV irradiation is the main mechanism used at the air–water interface. Indeed, UV light has the advantage of simplicity of use, avoiding the introduction of a cross-linking agent in the subphase and allowing a spatial control of the reaction at a local scale .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have also succeeded in the introduction of various functional groups such as redox species, aromatic chromophores, and chiral groups into the polymer LB films as a comonomer of DDA. A few examples of cross-linkable polymer LB films, for example, poly(styrene- co -maleic anhydride) derivatives for electron beam resists, poly(vinylpyridine) derivatives for patterning, and poly(vinyl acetal) and polyglutamate derivatives for thermal stability, have been reported. No reports on molecular patterning using cross-linkable polymer LB films are available in the literature to date.…”
Section: Introductionmentioning
confidence: 99%
“…The master curves represent the frequency dependence at a constant temperature, which can cover a wide temperature range. The shift factor a T employed for the time-temperature superposition follows the WLF equation: where C 1 and C 2 are constants and T 0 is a reference temperature. As shown in Figure , the plot of −( T − T 0 )/log a T versus T − T 0 gave straight lines.…”
Section: Resultsmentioning
confidence: 99%